Silkworm Cocoon: Dual Functions as a Traditional Chinese Medicine and the Raw Material of Promising Biocompatible Carriers - Zhijie Tian; Chuncao Zhao; Ting Huang; Lining Yu; Yijie Sun; Yian Tao; Yunfeng Cao; Ruofei Du; Wenhui Lin; Jia Zeng (MDPI AG, 2024)
The silkworm cocoon (SC), both as a traditional Chinese medicine and as the raw material for biocompatible carriers, has been extensively used in the medical and biomedical fields. This review elaborates on the multiple functions of SC, with an in-depth analysis of its chemical composition, biological activities, as well as its applications in modern medicine. The primary chemical components of SC include silk fibroin (SF), silk sericin (SS), and other flavonoid-like bioactive compounds demonstrating various biological effects. These include hypoglycemic, cardioprotective, hypolipidemic, anti-inflammatory, antioxidant, and antimicrobial actions, which highlight its potential therapeutic benefits. Furthermore, the review explores the applications of silk-derived materials in drug delivery systems, tissue engineering, regenerative medicine, and in vitro diagnostics. It also highlights the progression of SC from laboratory research to clinical trials, emphasizing the safety and efficacy of SC-based materials across multiple medical domains. Moreover, we discuss the market products developed from silk proteins, illustrating the transition from traditional uses to contemporary medical applications. This review provides support in understanding the current research status of SC and the further development and application of its derived products.